2009
DOI: 10.1007/s12192-008-0094-5
|View full text |Cite
|
Sign up to set email alerts
|

Preinduction of HSP70 promotes hypoxic tolerance and facilitates acclimatization to acute hypobaric hypoxia in mouse brain

Abstract: It has been shown that induction of HSP70 by administration of geranylgeranylacetone (GGA) leads to protection against ischemia/reperfusion injury. The present study was performed to determine the effect of GGA on the survival of mice and on brain damage under acute hypobaric hypoxia. The data showed that the mice injected with GGA survived significantly longer than control animals (survival time of 9.55 +/- 3.12 min, n = 16 vs. controls at 4.28 +/- 4.29 min, n = 15, P < 0.005). Accordingly, the cellular necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Hsp70 proteins are produced mainly in endothelial cells, in the core of infarcts in the cells that are most resistant to ischemia, in glial cells at the edges of infarcts, and in neurons outside the areas of infarction (479). It has been suggested that this neuronal expression of Hsp70 outside an infarct can be used to define the ischemic penumbras, which means the zone of protein denaturation in the ischemic areas; consistently in in vivo transgenic mice overexpressing Hsp70, compared to wild-type mice in a middle cerebral artery occlusion model of permanent cerebral ischaemia, it has been demonstrated that overexpression of Hsp70 reduces the overall lesion size and also limits the tissue damage within the lesion (479).…”
Section: Hsps and Neuroprotectionmentioning
confidence: 99%
“…Hsp70 proteins are produced mainly in endothelial cells, in the core of infarcts in the cells that are most resistant to ischemia, in glial cells at the edges of infarcts, and in neurons outside the areas of infarction (479). It has been suggested that this neuronal expression of Hsp70 outside an infarct can be used to define the ischemic penumbras, which means the zone of protein denaturation in the ischemic areas; consistently in in vivo transgenic mice overexpressing Hsp70, compared to wild-type mice in a middle cerebral artery occlusion model of permanent cerebral ischaemia, it has been demonstrated that overexpression of Hsp70 reduces the overall lesion size and also limits the tissue damage within the lesion (479).…”
Section: Hsps and Neuroprotectionmentioning
confidence: 99%
“…Mice were acclimatized in the chambers in room air for 30 min to 1 h before experiments. Two altitudes were selected based on trials and previous reports (Zhang et al 2004(Zhang et al , 2009) to create hypoxic conditions in the chambers: (1) 9,500 m (5.2% O 2 ) at a velocity of approximately 45 m/s for lethal acute hypobaric hypoxia, under which untreated mice died in a relatively uniform time period, and (2) the altitude of 8,300 m (7.0% O 2 ) at a velocity of approximately 20 m/s for sublethal acute hypobaric hypoxia, as it was severe enough to induce typical hypoxic organ injuries yet allowed the mice to survive so that hypoxia-induced changes in permeability of BBB, histological pathology, and the level of protein could be analyzed (Zhang et al 2009). …”
Section: Hypobaric Hypoxiamentioning
confidence: 99%
“…Shrivastava et al [22] developed a model of acute hypobaric hypoxia in rats with a simulated altitude of 10,668 m. During the experiment, the agonal breathing time and LD in hypoxia were recorded. The same method was also applied to mice, which were exposed to an altitude of 10,000 m and hypoxia simulation at a rate of 50 m/s for 15 min; the absolute apnea and death time were registered [28]. Lukyanova et al [13] and Mironova et al [16] modeled acute hypobaric hypoxia at a simulated altitude of 11,500 m and registered the onset of agonal breathing time.…”
Section: Discussionmentioning
confidence: 99%